Population collapse of a Gondwanan conifer follows the loss of Indigenous fire regimes in a northern Australian savanna - Bowman, David M. J. S.; Williamson, Grant J.; Johnston, Fay H.; Bowman, Clarence J. W.; Murphy, Brett P.; Roos, Christopher I.; Trauernicht, Clay; Rostron, Joshua; Prior, Lynda D. (Scientific reports, 2022)
Colonialism has disrupted Indigenous socioecological systems around the globe, including those supported by intentional landscape burning. Because most disruptions happened centuries ago, our understanding of Indigenous fire management is largely inferential and open to debate. Here, we investigate the ecological consequences of the loss of traditional Aboriginal fire management on fire-exposed savannas on the Arnhem Plateau, northern Australia, using the fire-sensitive conifer Callitris intratropica as a bio-indicator. We contrast Kakadu National Park, where traditional Aboriginal fire management was severely disrupted during the early twentieth century following Aboriginal relocation to surrounding settlements, and an adjacent Aboriginal estate where traditional Aboriginal fire management endures. Since 2006, traditional Aboriginal fire management at this site has been overlaid by a program of broad-scale institutionalized burning in the early dry season, designed to reduce greenhouse emissions. Using remote sensing, field survey, and dendrochronology, we show that on the Aboriginal estate, C. intratropica populations depend on the creation of a shifting patch mosaic of long unburned areas necessary for the recruitment of C. intratropica. However, the imposition of broad-scale fire management is disrupting this population patch dynamic. In Kakadu, there have been extreme declines of C. intratropica associated with widespread fires since the mid twentieth century and consequent proliferation of grass fuels. Fire management in Kakadu since 2007, designed to increase the size and abundance of patches of unburned vegetation, has not been able to reverse the population collapse of C. intratropica . Our study demonstrates that colonial processes including relocation of Indigenous people and institutional fire management can have deleterious consequences that are nearly irreversible because of hysteresis in C. intratropica population dynamics.